Examining Individual Tendency to Respond to Phishing E-Mails from the Perspective of Protection Motivation Theory - Diman, Allen Peter; T.K.A, Rahman (2023)
Phishing e-mails are major cyber threats not only to organisations but also to individuals. In many cases of reported phishing incidents, individuals fall prey to the trap of phishing e-mails because they believe the e-mails they received are legit. Previous studies have identified individual personality traits as one of the factors that can cause a person to become a victim of phishing attacks. Separately, different studies have also revealed that individuals’ handling of phishing threats and their actions to cope with such threats as other factors that can lead to a similar problem. To help understand the reason why certain types of personality traits are more inclined to respond to phishing e-mails, this study examined the role of individual protection motivation as the possible determinant that could further explain the relationships between personality traits and an individual’s response to phishing e-mails. The findings from 400 analysed data revealed that different personality traits except the trait of openness, exhibit different levels of perception in terms of their respective protection motivation. The study also found that individuals' tendency to respond to phishing e-mails depends on how they perceive the phishing threats and how they cope with such threats. Specifically, analysis of the results revealed that individuals with the trait of neuroticism have a high likelihood of responding to phishing emails. The study contributes to the body of knowledge by expanding the application of the Protection Motivation Theory to explain why certain types of personality traits have a higher tendency to respond to phishing e-mails than others. To avoid becoming phishing victims, individuals and as well as organisations should, therefore, put in greater efforts to ensure effective and sufficient coping strategies are in place to counter such threats. The implementation of anti-phishing training and phishing awareness campaigns can facilitate the attainment of this objective.